PERCERAIAN DAN AKIBATNYA TERHADAP PENDIDIKAN ANAK Studi kasus pada Keluarga Etnis Batak Toba di Kota Medan - Widya Kristina Marbun (Departemen Sosiologi Universitas Sumatera Utara, 2013)
Marriage aiming to announce and give a new status to the spouses to others that the couples accepted and recognized status as a lawful spouse, whether religious or customary state with a series of rights and obligations to be run by them, so he acted as a husband while she acted as his wife. But because there are conflicts caused by external and internal factors family, there was a divorce. Parental Divorce greatly affects their children and also affect their children's education. Writing research using case study analysis, qualitative. The survey results revealed that the effect of divorce for the Batak Toba greatly impacted the education of their children, where the children of divorce can be a school dropout or a mess. This is because two factor the lack of motivation and attention of parents who are divorced to his son, and the second is economic faktors single parents who are able to finance their children's school. Keywords: Divorce, due to divorce, child education